Casein kinase I-like protein kinases encoded by YCK1 and YCK2 are required for yeast morphogenesis. - Robinson, L C (1993)
Casein kinase I is an acidotropic protein kinase class that is widely distributed among eukaryotic cell types. In the yeast Saccharomyces cerevisiae, the casein kinase I isoform encoded by the gene pair YCK1 and YCK2 is a 60- to 62-kDa membrane-associated form. The Yck proteins perform functions essential for growth and division; either alone supports growth, but loss of function of both is lethal. We report here that casein kinase I-like activity is associated with a soluble Yck2-beta-galactosidase fusion protein in vitro and that thermolabile protein kinase activity is exhibited by a protein encoded by fusion of a temperature-sensitive yck2 allele with lacZ. Cells carrying the yck2-2ts allele arrest at restrictive temperature with multiple, elongated buds containing multiple nuclei. This phenotype suggests that the essential functions of the Yck proteins include roles in bud morphogenesis, possibly in control of cell growth polarity, and in cytokinesis or cell separation. Further, a genetic relationship between the yck2ts allele and deletion of CDC55 indicates that the function of Yck phosphorylation may be related to that of protein phosphatase 2A activity.